Serologic evidence of avian influenza virus infections among Nigerian agricultural workers1. Issue 4 (8th February 2013) - Okoye, John; Eze, Didacus; Krueger, Whitney S.; Heil, Gary L.; Friary, John A.; Gray, Gregory C.
Abstract Nigeria has had multiple incursions of highly pathogenic avian influenza A (HPAI) H5N1 virus into its poultry population since 2006. This study aimed to determine if Nigerians exposed to poultry had evidence of avian influenza virus transmission to man. Between 2008 and 2010, 316 adult farmers and open market workers and 54 age‐group matched, non‐animal exposed controls were enrolled in a prospective, population‐based study of zoonotic influenza transmission in four towns in southeastern Nigeria. Questionnaire data and sera obtained at the time of enrollment were examined for evidence of previous infection with 10 avian influenza virus strains. Serologic studies on sera collected at the time of enrollment showed modest evidence of previous infection with three avian‐origin influenza viruses (H5N1, H5N2, and H11N1) and one avian‐like H9N2 influenza virus, with eight (2.4%) of animal‐exposed subjects and two (3.7%) unexposed subjects having elevated microneutralization assay antibody titer levels (ranging from 1:10 to 1:80). Statistical analyses did not identify specific risk factors associated with the elevated antibody titers observed for these zoonotic influenza viruses. These data suggested only occasional virus transmission to humans in areas thought to have been enzootic for avian influenza virus. Prospective data from this cohort will help the authors to better understand the occurrence of zoonotic infections due to avian influenza viruses in Nigeria. J. Med. Virol. 85:670–676, 2013. © 2013 Wiley Periodicals, Inc.